Iconografia, arte e devoção : aspectos do legado material e imaterial em torno de Antonio Vicente Mendes Maciel, o beato Antonio Conselheiro = Iconography, art and devotion: aspects of the material and immaterial legacy around of the Antonio Vicente Mendes Maciel, the blessed Antonio Conselheiro - Santos, Jadilson Pimentel dos, 1975- (2017)
Orientador: Mauricius Martins Farina